Bank frauds causes and preventions: an empirical analysis - Ovuakporie, Vincent (Ibadan, Nigeria : Att Books, 1994)
This book is a documentation of various fraud investigations in which the author was involved.
Includes bibliographical references
rua 24/11/16
Loans
Keywords: Banks and banking; Embezzlement; Bank fraud; Nigeria